2001
DOI: 10.1007/s002040100248
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytochrome P450 2E1 in normal human bronchial epithelial cells and activation by ethanol in culture

Abstract: Serum-free primary cultures of human bronchial epithelial cells and freshly isolated samples of human bronchial epithelium were used to investigate basal expression of the cytochrome P450 enzyme CYP2E1 and its activation or induction by ethanol in bronchial epithelial cells. The cultures consisted of > or =95% cells of epithelial characteristics as determined by transmission electron microscopy and immunohistochemical staining. Monolayers were obtained from explants over a period of several months via transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…Moreover, ethanol treatment increased CYP2E1 activity in short-term cultures of isolated bronchial epithelium [152]. CYP2E1 expression is controlled by methylation of dinucleotide CpG residues in the 5' end of the CYP2E1 gene in the lung [167].…”
Section: Lung and Respiratory Tract 61 Constitutive Expression Of Cmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, ethanol treatment increased CYP2E1 activity in short-term cultures of isolated bronchial epithelium [152]. CYP2E1 expression is controlled by methylation of dinucleotide CpG residues in the 5' end of the CYP2E1 gene in the lung [167].…”
Section: Lung and Respiratory Tract 61 Constitutive Expression Of Cmentioning
confidence: 95%
“…Conflicting results have been published for some CYP enzymes concerning their expression in human lung tissue at the mRNA, protein and activity levels [22,146,150]. In addition, there are also CYP enzymes which have been detected at the mRNA level, but not at the protein level (such as CYP2F1 in bronchial epithelium [152]) or which have been detected at the protein, but not at the activity level (e.g. CYP3A4) [153].…”
Section: Lung and Respiratory Tract 61 Constitutive Expression Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…By far the greatest amount of information has been gathered concerning the induction of CYP 1A1; some reports have also shown that CYP 1B1, 2E1 and 2J may be inducible in the lung (Ding and Kaminsky, 2003;Hukkanen et al, 2002a;Runge et al, 2001;Xie et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, posttranslational activity measurement is critically important for some isozymes. For example, the regulation of CYP2E1 expression is complex and appears to involve different mechanisms including gene transcription and posttranscriptional mRNA stabilization (Runge et al 2001). In addition to individual CYP isozyme activities, a complete assessment for induction should include cytochrome P450 content and NADPH-cytochrome P450 oxidoreductase (CytoR).…”
Section: The Assessment Of Cyp Activitiesmentioning
confidence: 99%